Greenhouse Fruit and Vegetable Picking Tourism Management Model Based on Circular Economy with Productive Waqf Approach to Support Food Independence of Ngajum Malang Prison - Ni`' Matul Istiqomah; Dwi Wulandari; Putra Hilmi Prayitno; Abdul Rahman Prasetyo; Ari Gunawan; Afis Baghiz Syafruddin; Widia Nur Indriati (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2025)
Food independence in prisons remains a significant challenge, particularly in meeting the nutritional needs of inmates in a self-sustaining manner. Using a circular economy approach and the utilization of productive waqf in Ngajum Prison, Malang, this article offers a solution to the problem of managing greenhouse-based fruit and vegetable picking tourism. In addition to focusing on agricultural products, this model integrates elements of social empowerment of inmates, green economy, and education. In greenhouse management, the concept of circular economy is applied. This involves utilizing organic waste for composting, recycling water, and optimizing energy and space to create an efficient and environmentally friendly closed-loop farming system. Meanwhile, agricultural land management no longer depends solely on the state budget, as the productive waqf method obtains sustainable funds from individuals, institutions, and philanthropic partners. Analysis of needs and observations at Ngajum Prison indicate that there is significant potential to integrate agricultural activities with rehabilitation programs and vocational skills-based job training. One way to increase public access to the results of prison-fostered work is through educational fruit and vegetable picking tourism. Additionally, the purpose of creating learning media, such as direct practice, videos, and modules, is to enhance participants' understanding and skills. The conceptualization of the model demonstrates that cooperation among technology, education, and social economy, through a circular and waqf approach, can provide a strong foundation for creating a sustainable agricultural ecosystem in prisons. This model is expected to be applied in other similar institutions to strengthen national food independence and support social transformation through productive rehabilitation.